Factors Affecting The Event Low Birth Weight (LBW) - Yulia Rosemawati; Ribkha Itha Idhayanti; Ayuningtyas Ayuningtyas; Bambang Sarwono (Poltekkes Kemenkes Semarang, 2023)
Infants with LBW are one of the risk factors that have a large enough contribution to perinatal death. LBW babies can experience mental and physical disorders at a later age of development. Many conditions cause babies to be born with low birth weight. The main cause is premature birth, other factors are born to mothers who have health problems during pregnancy (preeclampsia, anemia, malnutrition), birth defects in babies, born to mothers with underweight, mother's age less than 17 years or more from 35 years, multiparous and twin pregnancies. Routine check-ups during pregnancy and meeting the nutritional needs of the mother are the best actions to prevent babies from being born with LBW (Setiaputri, 2021). Data from the Magelang District Health Office for 2021, there were 737 cases of LBW from 16,263 births. The Pakis Health Center is one of the areas that has high LBW cases, namely 44 out of 670 births and experienced an increase in 2022 as many as 52 (7.53%) LBW cases out of 690 birth. The purpose of this study was to determine the factors that influence the incidence of LBW in the Working Area of the Pakis Health Center. The method used is quantitative with a retrospective approach. The sampling technique used purposive sampling with the slovin formula obtained 253 respondents. The analysis used is univariate using frequency distribution and bivariate using Spearman Rank. The results showed that there was a relationship between maternal age (0.001), parity (0.015), gestational age (0.000), ANC visits (0.003), nutritional status (0.000), anemia (0.000) and preeclampsia (0.000) with the incidence of LBW. Health workers are expected to improve early detection through ANC, one of which is by conducting screening so that treatment can be given earlier